Up in the Air? : The Future of Public Service Media in the Western Balkans - Marko, Davor; Castro Herrero, Laia; Puppis, Manuel, 1977-; Jusić, Tarik (Book collections on Project MUSE., 2021)
The agenda for transition after the demise of communism in the Western Balkans made the conversion of state radio and television into public service broadcasters a priority, converting mouthpieces of the regime into public forums in which various interests and standpoints could be shared and deliberated. There is general agreement that this endeavor has not been a success. Formally, the countries adopted the legal and institutional requirements of public service media according to European standards. The ruling political elites, however, retained their control over the public media by various means.0Can this trend be reversed? Instead of being marginalized or totally manipulated, can public service media become vehicles of genuine democratization? 0A comparison of public service media in seven countries (Albania, Bosnia & Herzegovina, Croatia, Kosovo, Montenegro, North Macedonia, and Serbia) addresses these important questions.